The Application of Artificial Intelligence in Policy Formulation (Intelligent Policy Formulation) - Askari, Mehdi; Rashidpoor, Ali; Etebarian, Akbar; Zamani, Farsad (AI and Tech in Behavioral and Social Sciences, 2025)
Since previous policies have failed to adequately address existing public issues in society and have often created new problems themselves, it is necessary to move towards utilizing new tools, such as artificial intelligence (AI), to enhance policymaking. This article aims to review the characteristics of artificial intelligence to answer the question of why its utilization is necessary in the policy formulation process. To achieve this objective, among 100 articles retrieved from Google Scholar, 30 articles were selected, and subsequently, 10 articles were analyzed using note-taking to identify AI characteristics applicable to policy formulation. Artificial intelligence possesses capabilities such as analytical power, recognition, learning, prediction, foresight, the creation of large databases, and neural networks. By leveraging these features, in addition to existing capabilities, it is possible to achieve more precise and higher-quality policies, thereby enabling intelligent policy formulation.